A framework for devolatilization breakdown in entrained flow gasification modeling. (1st January 2017) - Rakhshi, A.; Wiltowski, T.
Abstract: A new framework for volatile breakdown is developed for entrained flow gasification modeling. The framework is based on an optimized solution of an under-determined system of equations formulated using a two-step Moore-Penrose generalized matrix approach. The approach permits the determination of the volatile composition using just the Proximate-Ultimate analysis data of coal. The method can be utilized for all coal types irrespective of origin. The accuracy and consistency of the framework is demonstrated by direct comparison with available devolatilization breakdown data. The overall performance of the framework is also appraised by incorporating it in a CFD simulation of an actual entrained flow gasifier. The reactor exit syngas composition from the simulation is favorably compared with available experimental data.